Предмет: Математика,
автор: oksanazinkevic010
найдите значение выражения 9*(х-3)-(х+3) при х=-4
Ответы
Автор ответа:
0
Пошаговое объяснение:
9(х-3)-(х+3)=9х-27-х-3=8х-30
Х= - 4
8×(-4)-30= - 32-30= - 62
Автор ответа:
0
Ответ:
-62
Пошаговое объяснение:
1) -4-3=-7
2) -4+3=-1
3) 9*(-7)=-63
4) -63-(-1)= -62
Похожие вопросы
Предмет: Английский язык,
автор: мила432
Предмет: Русский язык,
автор: Аноним
Предмет: Английский язык,
автор: заремаБ
Предмет: Математика,
автор: Nastyatrrrrrrrrr
Предмет: Алгебра,
автор: arseniy3303